Simultaneous Determination of Arsenic, Cadmium, Calcium, Chromium, Cobalt, Copper, Iron, Lead, Magnesium, Manganese, Molybdenum, Nickel, Selenium, and Zinc in Fertilizers by Microwave Acid Digestion and Inductively Coupled Plasma-Optical Emission Spectrometry Detection: Single-Laboratory Validation of a Modification and Extension of AOAC 2006.03. (27th November 2019) - Webb, Sharon; Bartos, James; Boles, Rhonda; Hasty, Elaine; Thuotte, Ethel; Thiex, Nancy J
Abstract: A single-laboratory validation study was conducted for the simultaneous determination of arsenic, cadmium, calcium, cobalt, copper, chromium, iron, lead, magnesium, manganese, molybdenum, nickel, selenium, and zinc in all major types of commercial fertilizer products by microwave digestion and inductively coupled plasma-optical emission spectroscopy analysis. This validation study proposes an extension and modification of AOAC 2006.03. The extension is the inclusion of calcium, copper, iron, magnesium, manganese, and zinc, and the modification is incorporation of hydrochloric acid in the digestion system. This dual acid digestion utilizes both hydrochloric and nitric acids in a 3 to 9 mL volume ratio/100 mL. In addition to 15 of the 30 original validation materials used in the 2006.03 collaborative study, National Institute of Standards and Technology Standard Reference Material 695 and Magruder 2009-06 were incorporated as accuracy materials. The main benefits of this proposed method are a significant increase in laboratory efficiency when compared to the use of both AOAC Methods 965.09 and 2006.03 to achieve